Ultrasound Fetal Weight Estimation in Diabetic Pregnancies - Pretscher, Jutta; Kehl, Sven; Stumpfe, Florian M.; Mayr, Andreas; Schmid, Matthias; Schild, Ralf L.; Beckmann, Matthias; Faschingbauer, Florian (Journal of Ultrasound in Medicine, 2020)
OBJECTIVES: To evaluate different formulas for estimating fetal weight in diabetic pregnancies. METHODS: This retrospective study evaluated the precision of ultrasound fetal weight estimation in 756 pregnancies complicated by gestational diabetes between 2002 and 2016. The estimated fetal weights (EFWs) were obtained within 7 days of delivery from 10 weight estimation formulas and were compared with pair-wise matched controls from 15,701 patients. The precision of the evaluated formulas for EFW was analyzed by median absolute percentage errors (MAPEs), mean percentage errors (MPEs), and proportions of estimates within 10% of actual birth weight. RESULTS: Among the tested formulas, the lowest MAPE was detected with formula I of Hadlock et al (Am J Obstet Gynecol 1985; 151:333-337), and the formula of Schild et al (Ultrasound Obstet Gynecol 2004; 23:30-35) had the highest proportion of estimates within the 10% range. The EFW in diabetic patients showed a slight trend toward overestimation in comparison with the matched controls (MPE estimates showed a trend toward more positive values). In most of the EFW formulas that were evaluated, no significant differences were detected in MAPEs and estimates within the 10% range. The MPE estimates with most formulas in both groups were close to zero. Overall, the differences between most of the evaluated formulas were small. CONCLUSIONS: Little evidence was found for differences in the accuracy of the EFW in diabetic pregnancies and controls. The Hadlock I formula showed the lowest MAPE, and the Schild formula had the highest proportion of estimates within the 10% range.
EVALuna2:212326